2022
DOI: 10.1007/s11883-022-01046-2
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Bias, or Both? The Contribution of Sex and Gender to the Disparity in Cardiovascular Outcomes Between Women and Men

Abstract: Purpose of Review Cardiovascular disease (CVD) is the leading cause of mortality and morbidity worldwide for both men and women. However, CVD is understudied, underdiagnosed, and undertreated in women. This bias has resulted in women being disproportionately affected by CVD when compared to men. The aim of this narrative review is to explore the contribution of sex and gender on CVD outcomes in men and women and offer recommendations for researchers and clinicians. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 73 publications
0
11
0
1
Order By: Relevance
“… 22 For instance, although the GBD strives to adjust for sources of bias inherent in self-reported data, such as recall bias and desirability bias, as well as non-sampling errors and differential diagnostic patterns, we recognise that the GBD methods are not able to entirely address and correct for all biases in reported data or fully control for differences in diagnostic likelihood for specific conditions. For example, the under-diagnosis and treatment of depression in males 52 and of cardiovascular diseases in females 53 have been previously discussed. Additionally, the effect of imbalanced or incomplete representation of population groups, such as the under-representation of men and some age groups in topic-specific surveys, can skew the accuracy of conclusions drawn regarding the health needs of all people.…”
Section: Discussionmentioning
confidence: 99%
“… 22 For instance, although the GBD strives to adjust for sources of bias inherent in self-reported data, such as recall bias and desirability bias, as well as non-sampling errors and differential diagnostic patterns, we recognise that the GBD methods are not able to entirely address and correct for all biases in reported data or fully control for differences in diagnostic likelihood for specific conditions. For example, the under-diagnosis and treatment of depression in males 52 and of cardiovascular diseases in females 53 have been previously discussed. Additionally, the effect of imbalanced or incomplete representation of population groups, such as the under-representation of men and some age groups in topic-specific surveys, can skew the accuracy of conclusions drawn regarding the health needs of all people.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent findings demonstrate a sex-specific interpretation of the connection between circulating cytokine levels and METS-IR in females 48 . Sex differences in fat distribution and sex-specific risk factors including menopause, reproductive endocrine disorders, and pregnancy complications may partially account for this phenomenon 49 . Collectively, understanding sex differences will aid in the development of individualized MACEs prevention and treatment interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, men considered their symptoms more seriously and were more likely to visit a cardiologist [ 71 ]. In similar reviews, women were found to be more likely to call 911 for a friend experiencing heart attack symptoms than for themselves and less likely to report their own symptoms [ 7 , 21 , 72 - 75 ]. The latter finding was confirmed by a survey that interviewed 1,000 American women who had reported their lack of awareness of CVDs being the main cause of death among women [ 74 ].…”
Section: Reviewmentioning
confidence: 99%